2020
DOI: 10.1186/s13020-020-00402-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor EB agonists from natural products for treating human diseases with impaired autophagy-lysosome pathway

Abstract: Autophagy is a highly conserved degradation process for long-lived intracellular proteins and organelles mediated by lysosomes. Deficits in the autophagy-lysosome pathway (ALP) have been linked to a variety of human diseases, including neurodegenerative diseases, lysosomal storage disorders, and cancers. Transcription factor EB (TFEB) has been identified as a major regulator of autophagy and lysosomal biogenesis. Increasing evidence has demonstrated that TFEB activation can promote the clearance of toxic prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…TFEB is a transcription factor, and acts as a primary regulator of autophagy, lysosomal genesis, lipid and energy metabolism, and the immune response (52)(53)(54)(55). Previous studies demonstrated that TFEB can advance neurodegenerative diseases, such as Parkinson's disease and Huntington's disease (56,57). TFEB also serves an important role in the metabolic response to starvation (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…TFEB is a transcription factor, and acts as a primary regulator of autophagy, lysosomal genesis, lipid and energy metabolism, and the immune response (52)(53)(54)(55). Previous studies demonstrated that TFEB can advance neurodegenerative diseases, such as Parkinson's disease and Huntington's disease (56,57). TFEB also serves an important role in the metabolic response to starvation (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Upon closure, mature Frontiers in Pharmacology frontiersin.org autophagosome engulfs the autophagic cargoes and subsequently fuses with lysosomes. Finally, the autophagic cargoes are metabolized by hydrolytic enzymes of lysosomes, and degraded contents are returned into the cytoplasm through lysosomal efflux permeases for reuse (Jing and Lim, 2012;Jin and Klionsky, 2014;Xu et al, 2020) (Figure 4).…”
Section: Molecular Mechanism Of Autophagy Pathwaymentioning
confidence: 99%
“…TFEB is closely associated with lysosome synthesis, impaired autophagic degradation, poor fusion of autophagosomes and lysosomes, and lysosomal dysfunction. The regulation mechanisms by TFEB and lysosomes may be central to autophagy regulation [ 114 ]. Lysosomal biosynthesis is tightly controlled by the cellular metabolic state and by signaling from lysosomal membrane-bound molecules.…”
Section: Mitophagymentioning
confidence: 99%